New Member of Editorial Board - Vitchev, Grazyna Rembielak (Serbian Journal of Management, 2012)
Dr. Grazyna Rembielak-Vitchev Senior Lecturer in Marketing, Director of School and College Liaison, Widening Participation Champion, Salford Business School BA(Hons) BSc(Hons) MA MSc PhD